(untitled) (Research, Society and Development, 2022)
This text reflects on the relationship between percussive music and education through the presentation and analysis of the biography of an artist-teacher (pedagogue) percussionist and drummer, member of the sceno-musical group Dona Zefinha (Itapipoca, Ceará, Brazil). The methodological path of this study is guided by the experiential approach that provides the perception of self-knowledge, while expanding the creation of self-referenced knowledge, in a continuous movement of self-training, related to the sociocultural context in which the subject enters. With all the analyzes carried out on the aforementioned artistic-educational trajectory of the author of this text, it is concluded that the perspective of self-education based on the autobiographical bias, potentiated the professional performance of the subject in focus, which emerged and perfected together with everyday artistic and educational practices, as a constitutive condition of the performance itself; a reflective process that developed in practice and also on it.